MECHANISMS FOR EXPANDING YOUTH PARTICIPATION IN PUBLIC LIFE IN UZBEKISTAN - Sarvar Otamuratov (Sciental Journals Publishing, 2025)
This article examines modern approaches to the implementation of youth policy in the country. It has been discovered that, in recent years, Uzbekistan has adopted a number of legal and regulatory acts aimed at comprehensive support for youth. It has been established that youth policy holds a priority position in the national development strategy, as evidenced by the inclusion of relevant provisions in the Constitution. It has been clarified that mechanisms for involving young people in public and political life are actively being developed through the creation of institutional platforms, support programs, and initiatives promoting social engagement. The patterns of state youth policy, its institutional framework, forms, and methods of implementation have been characterized. The impact of the ongoing reforms on the development of civic engagement, patriotism, and political culture among youth has been considered. The article concludes that strengthening cooperation between the state, society, and youth organizations is essential for the sustainable development of civil society.
Keywords: Youth policy, civic engagement, public life, youth participation, Uzbekistan, youth organizations, reforms, Constitution, political culture.